Strategy and narrative in higher education - Holstein, Jeannie C.A.; Starkey, Kenneth; Wright, Mike (SAGE Publications, 2016)
In this paper we apply the idea of narrative to strategy and to the development of strategy in the higher education context. We explore how strategy is formed as an intertextual narrative in a comparative study of higher education (HE) in the UK context. Existing research suggests that competition between narratives, such as that in HE, should be problematic in strategy terms. We show that this is not necessarily the case. Unlike in other settings where new strategy narratives tend to drive out previous narratives, in HE it is the ongoing interaction between historical and new narratives that gives the content of strategy its essential voice. We show how apparently competing narratives are accommodated though appeals to emotion and values. The maintenance of strategic direction requires hope and a synthesis of societal values that maintains access to the past, the future, and multiple narrators. This approach helps us understand how universities perform the complex task of adapting the strengths of the university’s past to the challenges of external policy developments in strategy formation.